1990
DOI: 10.1002/acp.2350040103
|View full text |Cite
|
Sign up to set email alerts
|

The unconscious transference effect: Are innocent bystanders ever misidentified?

Abstract: Unconscious transference refers to an eyewitness's misidentification of an innocent bystander for a criminal perpetrator because of the witness's exposure to the bystander in another context. In a series of five field studies involving 330 retail store clerks and 340 students, five retention intervals from 2 hours to 2 weeks, seven bystander-perpetrator intervals from 2 minutes to 2 weeks, three line-up types, two levels of line-up similarity, four different bystanders and four different targets, with one exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
2
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 33 publications
7
97
2
1
Order By: Relevance
“…As such, the original encoding events may have been rather indistinct, therefore inflating the likelihood of obtainingtransference errors, as compared with the real world (cf. Read et al, 1990). Similarly, our use of a mug shot test phase, although useful for our theoretical purposes, may not transfer well to real-world cases in which participants see bystanders in other ways, not requiring judgments about familiarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the original encoding events may have been rather indistinct, therefore inflating the likelihood of obtainingtransference errors, as compared with the real world (cf. Read et al, 1990). Similarly, our use of a mug shot test phase, although useful for our theoretical purposes, may not transfer well to real-world cases in which participants see bystanders in other ways, not requiring judgments about familiarity.…”
Section: Discussionmentioning
confidence: 99%
“…In four field studies, Read, Tollestrup,Hammersley, McFadzen, and Christensen (1990) examined retail staff's memory for customers who had made unusual requests (e.g., asking for a $5 note in return for 20 quarters). The lineups contained bystanders who had made different requests, and no unconscious transference effects were shown at all.…”
Section: The Poor Source Retrieval Explanation Of Unconscious Transfementioning
confidence: 99%
“…This suggests that people are less likely to remember the circumstances in which they encountered an individual of a different race. Research into bystander misidentification (Read et al, 1990;Ross et al, 1994) and mugshot exposure (Deffenbacher et al, 2006;Dysart et al, 2001) has shown that people can and do make mistakes concerning the context in which a face has been encountered. This study shows that these transference errors may be more likely in cross-race identifications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, participants may be unable to accurately remember whether a target individual was an assailant or a bystander at a crime (Read et al, 1990;Ross, Ceci, Dunning, & Toglia, 1994), or may be unable to recall whether an individual was seen at a crime scene or later, in a photo array (Deffenbacher, Bornstein, & Penrod, 2006;Dysart, Lindsay, Hammond, & Dupuis, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation